PERAN GURU KELAS DALAM MENCEGAH PERILAKU BULLYING PADA SISWA DI SD NEGERI 14 PANGKALPINANG - Anggrea Noveri, Edis Anggrea Noveri; Akhmad Maulana, Said; Hanif Setiawan, Rifki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Bullying includes acts that upset or hurt people who are seen to be weaker or more vulnerable, including verbal and nonverbal acts of aggression committed by individuals or groups. The main types of bullying behaviour are relational, physical, verbal, and cyberbullying. Students may suffer grave repercussions if bullying is not handled. Classroom teachers hold a pivotal role in preventing bullying among students. As a result, this research examines the frequency of bullying at SD Negeri 14 Pangkalpinang and evaluates the role that classroom instructors may play in preventing it. A descriptive qualitative strategy was used in this study. Interviews, observations, and documentation were used to gather data. The Miles and Huberman methodology, which covers data reduction, data presentation, and conclusion formulation or verification, was followed in the data analysis. Source triangulation was used to guarantee the veracity of the data. The results at SD Negeri 14 Pangkalpinang indicated the presence of several forms of verbal bullying, such as mockery related to ethnicity, religion, parents' names, and physical appearance. Physical bullying, including pushing, hitting, and kicking, as well as relational bullying, was also identified. Classroom teachers were found to be effective in reducing bullying among students by fulfilling their roles as instructors, advisors, educators, and providers of social support. Keywords: Bullying, Role of Classroom Teachers, Prevention